Monoterpene substituted thiazolidin-4-ones as novel TDP1 inhibitors: Synthesis, biological evaluation and docking. (1st October 2022) - Ivankin, Dmitry I.; Dyrkheeva, Nadezhda S.; Zakharenko, Alexandra L.; Ilina, Ekaterina S.; Zarkov, Timofey O.; Reynisson, Jóhannes; Luzina, Olga A.; Volcho, Konstantin P.; Salakhutdinov, Nariman F.; Lavrik, Olga I.
Graphical abstract: Abstract: Tyrosyl-DNA phosphodiesterase 1(TDP1) is a promising target for a new therapy in oncological disease as an adjunct to topoisomerase 1 (TOP1) drugs. In this paper, novel thiazolidin-4-one derivatives with a benzyl and monoterpene substituents were synthesized. Compounds with a monoterpene fragment attached via a phenyloxy linker were active against TDP1 with IC50 values in the 1 ÷ 3 μM range, while direct attachment of monoterpene moiety to the thiazolidin-4-one fragment had no activity. Molecular modelling predicted two plausible binding modes of the active compounds both effectively blocking access to the catalytic site of TDP. At non-toxic concentrations the active ligands potentiated the efficacy of the TOP1 poison topotecan in human cervical cancer HeLa cells, but not in non-cancerous HEK293A cells.